Cone Beam CT Study of Temporal Crest Canal - Mahvash Hasani; Shoaleh Shahidi; Shahrzad Alsadat Shamszade (Shiraz University of Medical Sciences, 2018)
Statement of the Problem: It is crucial for clinicians to be certain about the location of mandibular canal and determine any anatomical variants relevant to it. The temporal crest canal (TCC) is a rare anatomical variant of mandibular canal that lack of awareness about its presence can complicate surgical procedures. Purpose: This study investigated the anatomical characteristics and prevalence of the TCC using CBCT. Materials and Method: This descriptive cross-section study evaluated 327 CBCTs (654 sides) from all the patients with various problems. TCC on sagittal and axial plans were identified and then classified into two types based on their configuration. The prevalence of TCC was calculated amongst men and women. Results: Six TCC (0.91%) were observed in 654 sides. We observed all 6 TCCs in females. One case (0.30%) was bilateral TCC, and the remaining four (1.22%) cases were unilateral TCC (two on the left and two on the right side). Considering the classification of TCC, five sides had presentation of type I and one case was type II based on Kawai et al. study. Conclusion: Three-dimensional images of CBCT data are useful in confirming the presence of TCC. TCC is considered as a clinically significant structure; therefore, this variation should be carefully investigated using reconstructed CBCT images.